The Sopranos - Edgerton, Gary R. (Gary Richard), 1952- (Book collections on Project MUSE., 2013)
From its premiere in 1999, The Sopranos captivated viewers with its easily relatable protagonist who has troubles at work and home, and went on to be one of the most critically successful shows in television history. By demonstrating that TV could be at once artistic and profitable, complex and engaging, edifying and entertaining, the series also redefined the prime-time drama. In this volume, the author delves into the entire run of The Sopranos, integrating the existing scholarly literature, while also going much further than previous sources in exploring the series' innovations and legacy.